Brassica rapa orphan gene BR1 delays flowering time in Arabidopsis - Jiang, Mingliang; Zhang, Yuting; Yang, Xiaolong; Li, Xiaonan; Lang, Hong (Frontiers in Plant Science, 2023)
Orphan genes are essential to the emergence of species-specific traits and the process of evolution, lacking sequence similarity to any other identified genes. As they lack recognizable domains or functional motifs, however, efforts to characterize these orphan genes are often difficult. Flowering is a key trait in Brassica rapa, as premature bolting can have a pronounced adverse impact on plant quality and yield. Bolting resistance-related orphan genes, however, have yet to be characterized. In this study, an orphan gene designated BOLTING RESISTANCE 1 (BR1) was identified and found through gene structural variation analyses to be more highly conserved in Chinese cabbage than in other available accessions. The expression of BR1 was increased in bolting resistant Chinese cabbage and decreased in bolting non-resistant type, and the expression of some mark genes were consist with bolting resistance phenotype. BR1 is primarily expressed in leaves at the vegetative growth stage, and the highest BR1 expression levels during the flowering stage were observed in the flower buds and silique as compared to other tissue types. The overexpression of BR1 in Arabidopsis was associated with enhanced bolting resistance under long day (LD) conditions, with these transgenic plants exhibiting significant decreases in stem height, rosette radius, and chlorophyll content. Transcriptomic sequencing of WT and BR1OE plants showed the association of BR1 with other bolting resistance genes. Transcriptomic sequencing and qPCR revealed that six flowering integrator genes and one chlorophyll biosynthesis-related gene were downregulated following BR1 overexpression. Six key genes in photoperiodic flowering pathway exhibited downward expression trends in BR1OE plants, while the expression of floral repressor AtFLC gene was upregulated. The transcripts of these key genes were consistent with observed phenotypes in BR1OE plants, and the results indicated that BR1 may function through vernalization and photoperiodic pathway. Instead, the protein encoded by BR1 gene was subsequently found to localize to the nucleus. Taken together, we first propose that orphan gene BR1 functions as a novel regulator of flowering time, and these results suggested that BR1 may represent a promising candidate gene to support the selective breeding of Chinese cabbage cultivars with enhanced bolting resistance.